Oral Manifestations in Monkeypox: A Scoping Review on Implications for Oral Health - Asmaa Wajeeh Issa; Nada Fayyad Alkhofash; Divya Gopinath; Sudhir Rama Varma (MDPI AG, 2023)
Background: The monkeypox outbreak in 2022 caused concern in the public. Infected patients usually present prodromal symptoms, such as lesions on their skin and mucous membranes, including the oral cavity. The current study aims to review the most common oral/perioral manifestations reported to date. Methods: A literature search was conducted in the PubMed, Research Gate, and Wiley Online Library databases, as well as in the Google search engine, using keywords related to the condition. Of the 56 publications identified, 30 were selected, including 27 case reports, two case series types, and one cross-sectional study published from 2003 to 2023 in endemic and non-endemic countries. Of the 54 patients in these studies, data on the oral symptoms and sites of monkeypox were interpreted from 47 patients. Results: Oral/perioral signs as one of the initial manifestations were reported in 23 out of 47 patients (48.93%). Out of the 47 patients with oral/perioral involvement, the most common signs/symptoms were sore throat, followed by ulcers, vesicles, dysphagia and odynophagia, and erythema. Conclusion: The most common oral symptom of monkeypox is sore throat, followed by ulcers. The symptoms usually occur in the pharynx/oropharynx, followed by the tonsils and tongue. Adequate knowledge about the characteristics of this virus and their association with the oral cavity is necessary, and could help oral health professionals to distinguish between different infections.